Energy Efficient Homes: The Energy and Water Connection - Nicholas W. Taylor; Brent Philpot; Kathleen C. Ruppert (EDIS)
FCS-3273, a 4-page fact sheet by Nicholas W. Taylor, Brent Philpot, and Kathleen C. Ruppert, describes the energy used for municipal water supply and waste water management, and the water used for energy production and strategies homeowners can use to reduce water use in the home. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.